Drama online jako sposób na aktywne poznawanie lektur w cyfrowym świecie - Agnieszka Kulig (Postscriptum Polonistyczne)
The article describes the possibilities of using social networking in education with an example of online drama (dramalike activities led in digital space). The theoretical assumptions of this method are described in the article as well as some examples of its practical realization. The conclusions drawn from scientific literature are enriched with personal reflections (based on the experience gained while working on Przedwiośnie by Stefan Żeromski).